2013
DOI: 10.1590/s1519-99402013000400008
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Pennisetum purpureum by Opuntia ficus-indica and Mimosa tenuiflora in the diet of lambs

Abstract: The objectives of this study were to quantify the apparent digestibility of the diet components and the performance of lambs consuming increasing levels of the balanced (weight) mixture of Opuntia ficus indica bran and Mimosa tenuiflora leaves and fine branches hay substituting 0, 33 and 67% of Pennisetum purpureum hay, in a 60% roughage fodder to 40% concentrate diet formulated to a daily live body weight gain of 150 g/animal. Experiment was carried out at UFCG facilities, in Patos-PB, using 18 non-emasculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Mineral matter content was not affected (P>0.05) by branch cutting intensity; it increased (P<0.05) from 5.53% in branches to 5.90% in sprouts (Table 3). Souza et al (2006) and França et al (2010) reported MM content of 8.08% and 9.85%, respectively, in fine branches of native M. glaziovii, while reports on MM content in branches of other trees, including fine branches of M. tenuiflora (CORDÃO et al, 2013;FORMIGA et al, 2011) and Ziziphus joazeiro (COSTA et al, 2010), reported it to range from 3.78% to 7.74%, respectively. Similarly, P. pyramidalis was observed to have MM content in the range 4.58% to 6.11% (GONZAGA NETO et al, 2001;MENDONÇA JÚNIOR et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mineral matter content was not affected (P>0.05) by branch cutting intensity; it increased (P<0.05) from 5.53% in branches to 5.90% in sprouts (Table 3). Souza et al (2006) and França et al (2010) reported MM content of 8.08% and 9.85%, respectively, in fine branches of native M. glaziovii, while reports on MM content in branches of other trees, including fine branches of M. tenuiflora (CORDÃO et al, 2013;FORMIGA et al, 2011) and Ziziphus joazeiro (COSTA et al, 2010), reported it to range from 3.78% to 7.74%, respectively. Similarly, P. pyramidalis was observed to have MM content in the range 4.58% to 6.11% (GONZAGA NETO et al, 2001;MENDONÇA JÚNIOR et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In general, forage from fine branches of trees shows high NDF and ADF contents (53.9%<NDF<84.1%, 46.5%<ADF<70.3%) (CORDÃO et al, 2013;COSTA et al, 2010;FORMIGA et al, 2011;). However, fine branches of the well-known, but soil and water demanding, Leucaena leucocephala (Lam) may result in forage with NDF and ADF contents of 30.8% and 14.3% , respectively, and those from the xerophilous native, Poincianella pyramidalis (Tul.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations